Computational Thinking: The Essential Skill for being Successful in Knowledge Science Research - Bachtiar, Adam Mukharil (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2023)
The VUCA world concept was established in 2016 as the new challenge universe in the 21st century. Humans live in Society 5.0 and the VUCA world simultaneously. The digital word has been a noisy word since then. There are a lot of requisite skills to be a survival kit for this kind of era. The VUCA world's affection is spreading in the way of thinking and creating innovation, especially in the research domain. As a newcomer, Knowledge Science should state the requisite skills for its researchers to conduct their research successfully. Many researchers offered computational thinking as a candidate for an essential skill to satisfy the effect of the VUCA world. This study was focused on conducting a descriptive analysis method based on several literature reviews for mapping how computational thinking can serve as a best practice for Knowledge Science research. This study successfully revealed the connection between Computational Thinking.